Application of the Autogenic Relaxation Method to Hypertension Sufferers in the Work Area of the Mekarmukti Health Center - Suanda Saputra (Jurnal Pengabdian Masyarakat Formosa, 2022)
Community service activities are carried out at the Posbindu Seroja working area of ​​the Mekarmukti Health Center, North Cikarang District, Bekasi Regency. This service activity is carried out with the aim of providing understanding to the public about hypertension and its non-pharmacological management by providing autogenic relaxation training methods with good/correct and directed techniques. Educational and training activities are tailored to the problems and needs faced by partners. The method of implementing community service activities starts from observing and identifying problems in the working area of ​​the Mekarmukti Health Center. Community service activities are carried out in October - November 2022. The results of the community service activities are that participants participate in activities from start to finish with enthusiasm, respondents have knowledge and understand about hypertension and its non-pharmacological management, and participants are able to practice/demonstrate autogenic relaxation techniques correctly according to with that exemplified by the servant.